The information and support needs of patients diagnosed with High Grade Glioma - Halkett, Georgia; Lobb, Elizabeth; Oldham, Lynn; Nowak, A. (Elsevier, 2009)
Objective: To understand patients' experiences of High Grade Glioma and identify and describe information and support needs along the disease trajectory. Methods: Semi-structured interviews were conducted with 19 patients. Data was analysed using grounded theory and the constant comparative method. Results: Four major themes were identified: (1) feelings of uncertainty around prognosis and quality of life; (2) the need for individualised information; (3) dependence on carers due to cognitive deficits, loss of balance and inability to drive; and (4) communication with health professionals around prognostic uncertainty and disease progression with communication barriers due to complex language deficits. Conclusion: Previous studies in HGG pre-date the current combined modality standard of care, or examined a mixed population. This study has found that patients with HGG have needs that differ from other patients with terminal malignancy and that these needs change over time with disease progression. Practice implications: This study has identified that patients with brain tumours may have unique needs. Health professionals need to clarify patients' information and support needs and be aware that these change over and within time.